(3QSGdI GdQVi hGdJSdje Edi cGaI GdehMOjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hEdi LejY ef Tc ai ehdGfG Ld PcQg hai hdjg bGFe GdReGf Ydjg GdSdGe ef YHO ehdGfG SHMGf bOQI s
(3BNQgG (B:s
(3Ch JXfhG Hg Xf GdShA aJchfhG ef GdNGSQjf ai GdOjf hgh MSHi hYdjg JhcdJ hgh fYe GdeYjf JeJ HMeO ehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds